Intimate partner violence education in Australian medical schools: has anything changed? - Alexandra Baum; Jodie Valpied; Jacqueline Kuruppu; Kelsey Hegarty (Elsevier, 2022)
Abstract Objectives: To describe current intimate partner violence (IPV) education delivery to Australian medical students, and the barriers influencing this delivery, including any changes in the quantity and nature of IPV education delivery since 2010. Methods: A cross‐sectional analysis of Australian medical schools providing primary medical degrees was conducted by identifying one staff member, from each of the disciplines of general practice, obstetrics and gynaecology, paediatrics, and where necessary, medical education, to complete an online survey. Results: Sixteen of the 17 medical schools provided IPV education, typically within the general practice or obstetrics and gynaecology curriculum. The median contact hour range was 3-6 hours. Key barriers included time constraints and resource shortages. The overall response rate was 89.5%. Conclusion: Most Australian medical students receive limited IPV education and there is substantial variability in the depth and content of education. The proportion of medical schools providing education and the number of contact hours has only slightly increased. Implications for public health: Effective identification and management of IPV by healthcare providers can significantly improve health outcomes for victims and training in IPV may improve attitudes, knowledge and clinical skills. The need to provide more consistent and comprehensive IPV training for future doctors remains, and it is feasible to include integrated IPV education programs within a crowded medical curriculum.